Wind and solar curtailment - Lew, Debra (2013)
High penetrations of wind and solar generation on power systems are resulting in increasing curtailment. Wind and solar integration studies predict increased curtailment as penetration levels grow. This paper examines experiences with curtailment on bulk power systems internationally. It discusses how much curtailment is occurring, how it is occurring, why it is occurring, and what is being done to reduce curtailment. This summary is produced as part of the International Energy Agency Wind Task 25 on Design and Operation of Power Systems with Large Amounts of Wind Power.